Hearing restoration and the stria vascularis: evidence for the role of the immune system in hearing restoration. Issue 5 (October 2021) - Samaha, Nadia L.; Almasri, Mohamad M.; Johns, J. Dixon; Hoa, Michael
Abstract : Purpose of review: This article reviews the current literature regarding the pathogenesis of immune-mediated sensorineural hearing loss, utilizes previously published single-nucleus transcriptional profiles to characterize cytokine and cytokine receptor expression in the adult stria vascularis cell types to support immune system interaction with the stria vascularis and reviews the current literature on immunomodulatory agents currently being used for hearing-restoration treatment. Recent findings: The literature review highlights recent studies that elucidate many cytokines and immune markers, which have been linked to various immune-mediated disease processes that have been observed with sensorineural hearing loss within the stria vascularis and highlights recent publications studying therapeutic targets for these pathways. Summary: This review highlights the current literature regarding the pathogenesis of immune-mediated hearing loss. The role of cochlear structures in human temporal bones from patients with immune-mediated sensorineural hearing loss are highlighted, and we review cytokine signalling pathways relevant to immune-mediated sensorineural hearing loss and localize genes encoding both cytokine and cytokine receptors involved in these pathways. Finally, we review immunomodulatory therapeutics in light of these findings and point to opportunities for the application of novel therapeutics by targeting these signalling pathways.